The effect of Attention Deficit and Hyperactivity Disorder on Antiretroviral Treatment and Appointment Adherence among adults living with HIV - Serhat Uysal; Hayriye Elbi; Gülşen Mermut; Ozen Onen Sertoz; Figen Kaptan; Demet Gülpek; Deniz Gokengin (Journal of Infection in Developing Countries)
Introduction: The most prominent characteristic of adult attention deficit hyperactivity disorder (ADHD) is impulsive behavior and deficits in executive functions, which require long-term organization and discipline. This may have serious implications in terms of adherence to treatment among adults living with HIV (PLWH). This study aimed to determine the prevalence of ADHD among non-perinatally infected PLWH and its effect on adherence to antiretroviral treatment (ART) and scheduled appointments.